2012
DOI: 10.1128/aac.05896-11
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Substrate Binding Conformation of β-Lactams and Insight into the Broad Spectrum of NDM-1 Activity

Abstract: New Delhi metallo-␤-lactamase 1 (NDM-1) is a key enzyme that the pathogen Klebsiella pneumonia uses to hydrolyze almost all ␤-lactam antibiotics. It is currently unclear why NDM-1 has a broad spectrum of activity. Docking of the representatives of the ␤-lactam families into the active site of NDM-1 is reported here. All the ␤-lactams naturally fit the NDM-1 pocket, implying that NDM-1 can accommodate the substrates without dramatic conformation changes. The docking reveals two major binding modes of the ␤-lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…A recent computational substrate docking study of various β‐lactam antibiotics into the active site of the NDM‐1 enzyme has also produced interesting results 81 . The poses of the docked substrates revealed two major modes of binding that were named “S” and “I” conformers.…”
Section: Metallo‐β‐lactamase Substrate Binding and Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent computational substrate docking study of various β‐lactam antibiotics into the active site of the NDM‐1 enzyme has also produced interesting results 81 . The poses of the docked substrates revealed two major modes of binding that were named “S” and “I” conformers.…”
Section: Metallo‐β‐lactamase Substrate Binding and Catalysismentioning
confidence: 99%
“…The poses of the docked substrates revealed two major modes of binding that were named “S” and “I” conformers. The S mode has the carbonyl oxygen of the amide of β‐lactam ring coordinated to Zn1 and the carboxylate of the fused ring coordinated with Zn2 and the bridging water/hydroxide positioned for nucleophilic attack and therefore this conformer is optimally positioned for catalysis 81 . The I mode contains the carboxylic acid of the fused ring coordinating with Zn1 and Zn2 and displacing the water/hydroxide and moves the β‐lactam amide group away from the metal ions thus creating an inhibitory binding mode.…”
Section: Metallo‐β‐lactamase Substrate Binding and Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 In B1MBLs, such as IMP-1 and NDM-1, the adjacent position 224 in so-called active site loop 10 (ASL-10) is a conserved lysine that plays a key role in substrate binding because of its proximity to the active site. 11,12 In the VIM enzymes, position 224 has more allelic variants: histidine in VIM-1, -4, -7, -11, and -12; tyrosine in VIM-2; and leucine in VIM-5 and -13. 13 Because the side chains of these residues are shorter and less basic than that of the lysine, R228, with its extended side chain, is hypothesized to replace K224 in interacting with the carboxylate moiety (C4 or C3) of β -lactam substrates.…”
mentioning
confidence: 99%
“…In the absence of experimental structures of MβL-ligand complexes, docking studies can provide insights into possible binding modes of inhibitors 38 and β-lactam substrates. 39, 40 These studies have shown that substituents with high electron density, such as, thiols, carboxylates, and carbonyl groups interact electrostatically with the zinc ions and the positively-charged Lys224 conserved in many B1 and B2 MβLs. 41, 42 Here we assessed the binding mode of β-phospholactam 1 to the different MβLs using docking.…”
mentioning
confidence: 99%